Regional Investment Analysis through Gross Fixed Capital Formation (GFCF) Components in the Gross Regional Domestic Product (GRDP) of Way Kanan Regency - Alvira Rizky Azzakia; Klara Srikandi Laia; Iskandar Muda (Yayasan Bayt Shufiya Nusantara, 2025)
Investment is an asset intended to obtain economic benefits such as interest, dividends and royalties, and social benefits, so that it can improve the government's ability to provide services to the community. Investment is reflected in the Gross Fixed Capital Formation (GFCF) component, which is part of the Gross Regional Domestic Product (GRDP). This study aims to analyze the development of GFCF in Way Kanan Regency during the 2020-2024 period connecting it to the investment accounting perspective, the method used is descriptive quantitative with secondary data obtained from the publication of GRDP according to Way Kanan Regency expenditure 2020-2024 published by BPS (Central Statistics Agency).